Ultrasonic measurement in variation of a degree of saturation in compacted bentonite. (December 2017) - Kimura, Shun; Kitayama, Kazumi; Kimoto, Kazushi; Kawamura, Katsuyuki; Kikura, Hiroshige
Abstract: Bentonite, which is a kind of clay, is considered as a candidate for a buffer material in a geological repository of the high-level radioactive waste. Bentonite could provide long-term isolation of the radioactive waste because of its high adsorption capacity, low water permeability and good swelling property. In the context of long-term safety of disposal management, understanding groundwater behavior in bentonite buffer is one of the important issues, related to evaluating its long-term performance. In order to understand water behavior in compacted bentonite, the ultrasonic measurement was focused on. However, Ultrasonic wave propagation in compacted bentonite has not been understood well. Therefore, in this study, high spatial measurement system with Laser Doppler Vibrometer was developed in order to observe the ultrasonic wave propagation in compacted bentonite specimen. Ultrasonic wave propagation in compacted bentonite surface was measured. As a result, ultrasonic wave reflection was observed on the boundary between two different degrees of saturation. Thus, the capability of the developed system for investigation of the wave propagation in compacted bentonite is confirmed.